Potential-Dependent Adsorption of CO and Its Low-Overpotential Reduction to CH3CH2OH on Cu(511) Surface Reconstructed from Cu(pc): Operando Studies by Seriatim STM-EQCN-DEMS. Issue 15 (15th November 2018) - Tsang, Chu F.; Javier, Alnald C.; Kim, Youn-Geun; Baricuatro, Jack H.; Cummins, Kyle D.; Kim, Jutae; Jerkiewicz, Gregory; Hemminger, John C.; Soriaga, Manuel P.
Abstract : Operando scanning tunneling microscopy first revealed that application of a CO2 -reduction potential to a Cu(pc) electrode in 0.1 M KOH resulted in the reconstruction of the selvedge to an x-layer stack of well-ordered Cu(100) terraces, Cu(pc)-x[Cu(100)]. Subsequent Cu↔Cu2 O oxidation-reduction cycles between −0.90 V and 0.10 V SHE converted the reconstructed region to a stepped Cu(S)-[3(100) × (111)], or Cu(511), surface. Differential electrochemical mass spectrometry showed that reduction of CO produced only CH3 CH2 OH at the lowest overpotential. Later application of STM and surface infrared spectroscopy uncovered a potential, above which no CO adsorption occurs. In this study, electrochemical quartz crystal nanobalance was combined with STM and DEMS as a prelude to the acquisition of CO coverages as continuous functions of concentration and potential; in heterogeneous catalysis, surface coverage are important since the reaction rate are functions of those quantities. Also equally critical is the knowledge of the packing arrangement at the onset of the reaction because, if "CO dimers" were indeed the precursors to C2+ products, reduction can only be initiated when the adlayer consists of closely packed CO; otherwise, dimerization will not transpire if the molecules were far apart. The results indicate that the catalysis lags the adsorption, and starts only when CO adsorption is saturated.